ELISA-Based Measurement of Antibody Responses and PCR-Based Detection Profiles Can Distinguish between Active Infection and Early Clearance of Borrelia burgdorferi - John J. Lazarus; Akisha L. McCarter; Kari Neifer-Sadhwani; R. Mark Wooten (Clinical and Developmental Immunology)
Borrelia burgdorferi is a spirochetal bacterium that causes Lyme disease. These studies address whether current research methods using either ELISA to detect seroconversion to B. burgdorferi antigens or PCR quantification of bacterial DNA within tissues can accurately distinguish between a productive infection versus a B. burgdorferi exposure that is rapidly cleared by the innate responses. Mice receiving even minimal doses of live B. burgdorferi produced significantly more B. burgdorferi-specific IgM and IgG than groups receiving large inocula of heat-killed bacteria. Additionally, sera from mice injected with varied doses of killed B. burgdorferi recognized unique borrelial antigens compared to mice infected with live B. burgdorferi. Intradermal injection of killed B. burgdorferi resulted in rapid DNA clearance from skin, whereas DNA was consistently detected in skin inoculated with viable B. burgdorferi. These data indicate that both ELISA-based serological analyses and PCR-based methods of assessing B. burgdorferi infection clearly distinguish between an established infection with live bacteria and exposure to large numbers of bacteria that are promptly cleared by the innate responses.